-2d+2=-7d-13

Simple and best practice solution for -2d+2=-7d-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2d+2=-7d-13 equation:


d in (-oo:+oo)

2-2*d = -7*d-13 // + -7*d-13

2-2*d-(-7*d)+13 = 0

7*d-2*d+2+13 = 0

5*d+15 = 0 // - 15

5*d = -15 // : 5

d = -15/5

d = -3

d = -3

See similar equations:

| 1+6d=d+1 | | 3a+3=-2a-12 | | 4t+7=5+5t | | 6k-6=3k+3 | | 4a+10=7a-2 | | 5-4k=5k+50 | | -4t+2=112+6t | | -2+t=2t-1 | | 5x+2=2x+26 | | -8+2m=-2m+12 | | x+4=6x+4 | | 7+6k=-7k+7 | | 2m+2=-7m+56 | | 3a+3=-5a-37 | | 10-4t=-3t+1 | | 2b-1=-b+29 | | 2w-3=-12+5w | | 9+x=5x-19 | | 10-7k=3k+10 | | -2t+2=7t-16 | | (3/8)/100 | | 6n-7=5n-3 | | -7+7a=-4a-106 | | -3m+2=m-2 | | 3/8/100 | | -8-7t=-4t-44 | | 5-n=2n+17 | | 10+7n=6n+14 | | 4m+8=6m-4 | | 4d+10=-38-2d | | -1-2b=-6b-21 | | -4a+4=6a-86 |

Equations solver categories